Development of Solar Chlorinator for Clean Water Disinfection for Communities - Beny Suyanto; Denok Indraswati (Aloha International Journal of Health Advancement (AIJHA), 2021)
This study aims to improve the performance of digital solar chlorinators to disinfect clean water for the community. In this experimental study, a digital solar chlorinator was made for disinfection of clean water by testing performance with variations in distances of 0 m, 500 m and 1000 m, resulting in residual chlorine < 0.7 ppm and E coli bacteria. Chlorinator specifications are: solar cell panels; DC Converter stabilizer and Digital current voltmeter; Control solar cell system and battery changer; battery; adjustable velocity; peristaltic pump (pump chlor) using geer bok; control switch internet system or internet controller semiconductor (ICS) that uses a modem; submersible pumps; digital peristaltic pump water flow regulator which is assembled in the system. Performance of chlorinator peristaltic pump discharge: 45 liters/day (85 gram/day of chlorine) at source water flow rate of 1.1 liters/second, the results obtained: residual chlorine at distances of 0 m, 500 m and 1000 m respectively: 0.56 ppm, 0.43 ppm and 0.28 ppm (meets the regulation of the minister of health). It is necessary to further investigate how long the level of resistance, service life, operation and maintenance of the chlorinator is needed. The performance of the solar cell chlorinator with digital devices makes it easier to operate and maintain and can be applied to various discharges. Keywords: digital solar chlorinator; chlorine; water sources; E coli